Factors Affecting Downhill Skiing Participation of Canadian Consumers - Yang, Yiqi (Université d'Ottawa / University of Ottawa, 2019)
According to Statistics Canada (2013), downhill skiing participation rates have declined from 14% in 1992 to 6% in 2010. Finding ways to counteract this decline by revitalizing interest in downhill skiing is necessary to avoid further negative effects on the economic sustainability of the ski industry in Canada. This study proposes a reliable and valid measuring instrument to identify current factors that affect ski participation among various segments of skier groups. An online questionnaire is developed using extended Shank and Lyberger’s (2015) sports consumption model. It consists of five sections. Data were collected in the winter of 2019 from a convenience sample of 150 university students (targeting 30 participants for each: non-skiers, former-, low-, moderate-, and high-frequency skiers). Reliability was tested using a test(T1)-retest(T2) method among the same participants with a 14-day interval, calculating correlations. Of the initial 64 items, only 29 showed sufficient reliability. Generally speaking, the internal and external factors showed higher correlations, while the situational factors showed very low correlations and all 15 situational items had to be dropped. The results revealed that internal constraints influence former and low-frequency skiers more than higher-frequency skiers and that all current skiers, particularly in the high-frequency group, were strongly driven by internal facilitators such as positive perceptions. Family and financial constraint as an external, facilitating factor appear to be equally important among all groups of ski participants. Culture, another external factor, acts as a constraint on non-skiers, former skiers and low-frequency skiers, but has significantly less effect on high-frequency skiers. Former skiers are most affected by financial constraints, although this factor is also a constraint for other groups, if to a lesser extent.
Keywords: Marketing; Consumer behaviour; Downhill skiing; Sports participation